Rapid detection and quantification of vibrio parahaemolyticus in prawns (Penaeus monodon) by real-time pcr - Sim,, Sherry (Universiti Malaysia Sarawak, UNIMAS, 2012)
Vibrio parahaemolyticus is one of the etiologic agents of human gastroenteritis associated with seafood consumption. Vibrio parahaemolyticus carries the hemolysin gene, tlh gene other than the virulence tdh and trh genes. This study is carried out to detect and quantify Vibrio parahaemolyticus in 25 shrimp samples by Real-Time PCR assay. In this study, Luria Broth (LB) used as enrichment media is added with 3% of NaCl. The isolation and detection of Vibrio parahaemolyticus was done on both Thiosulphate Citrate Bile salt Sucrose (TCBS) agar and CHROMAgar Vibrio (CV). Next, Polymerase Chain Reaction (PCR) was carried out to confirm the absence of Vibrio parahaemolyticus in the Tilapia fish (Oreochromis niloticus) as the spiked sample. Furthermore, PCR also carried out to test the specificity of Vibrio parahaemolyticus tlh gene primers. Thirteen shrimp samples showed positive occurrence of Vibrio parahaemolyticus from the Real-Time PCR assay.